2002
DOI: 10.1126/science.1069609
|View full text |Cite
|
Sign up to set email alerts
|

Melanopsin-Containing Retinal Ganglion Cells: Architecture, Projections, and Intrinsic Photosensitivity

Abstract: The primary circadian pacemaker, in the suprachiasmatic nucleus (SCN) of the mammalian brain, is photoentrained by light signals from the eyes through the retinohypothalamic tract. Retinal rod and cone cells are not required for photoentrainment. Recent evidence suggests that the entraining photoreceptors are retinal ganglion cells (RGCs) that project to the SCN. The visual pigment for this photoreceptor may be melanopsin, an opsin-like protein whose coding messenger RNA is found in a subset of mammalian RGCs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

65
2,005
4
37

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 2,320 publications
(2,111 citation statements)
references
References 29 publications
65
2,005
4
37
Order By: Relevance
“…Moreover, octopus rhodopsin bears an evolutionary similarity to melanopsin (Oshima, 2001), which is expressed in SCN-projecting RGCs in the rat (Gooley et al, 2001;Hattar et al, 2002;Hannibal et al, 2002). Melanopsin is thought to form a retinal-based photopigment, and its sequence displays several hallmarks of invertebrate opsins, including a tyrosine counter-ion for the retinal Schiff's base, instead of the glutamate that is characteristic of vertebrate opsins (Provencio et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, octopus rhodopsin bears an evolutionary similarity to melanopsin (Oshima, 2001), which is expressed in SCN-projecting RGCs in the rat (Gooley et al, 2001;Hattar et al, 2002;Hannibal et al, 2002). Melanopsin is thought to form a retinal-based photopigment, and its sequence displays several hallmarks of invertebrate opsins, including a tyrosine counter-ion for the retinal Schiff's base, instead of the glutamate that is characteristic of vertebrate opsins (Provencio et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In striking contrast to their counterparts projecting to the primary visual targets (the dorsal lateral geniculate nucleus and the superior colliculus), SCN-projecting RGCs exhibit light responses independent of rod-and cone-driven synaptic input . Furthermore, the majority of these neurons express the novel photopigment melanopsin (Provencio et al, 2000;Gooley et al, 2001;Hattar et al, 2002;Hannibal et al, 2002). As an essential part of the neural pathway from the retina to the SCN, these RGCs play a critical role in generating and shaping retinal output to the circadian system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing wildtype mice with ocular mutants lacking rods and cones, Lupi et al (2012) showed a higher impact of the intrinsic aging effects, rather than degeneration of photoreceptors, on IGL and SCN activation. However, they did not study this relationship with melanopsin-based photosensitive retinal ganglion cells (pRGCs), which forms RHT (Gooley et al 2001;Hattar et al 2002). It should be noted that we used an albino rat animal model, which has an abnormally increased predominance of contralateral retinofugal projections (Fleming et al 2006).…”
Section: Discussionmentioning
confidence: 97%
“…Samer Hattar, a neuroscientist at Johns Hopkins University in Baltimore, Maryland, and his colleagues found that as many as 1% of the cells in the mouse ganglion layer express melanopsin, which is most sensitive to blue light 6 . David Berson, a neuroscientist at Brown University in Providence, Rhode Island, and his lab showed that these cells, ipRGCs, detect light on their own and reach into the brain's pacemaker, the suprachiasmatic nucleus 7 .…”
Section: Rods and Cones Dethronedmentioning
confidence: 99%